A review of proposed mechanisms for neurodegenerative disease - Kelser, Benjamin M.; Teichner, Eric M.; Subtirelu, Robert C.; Hoss, Kevin N. (Frontiers in Aging Neuroscience, 2024)
I am pleased to again submit our manuscript titled "A Careful Dive into the Synaptic Spread and Selective Vulnerability Hypotheses" to Frontiers in Aging Neuroscience. This review delves into the critical debate between the synaptic spread and selective vulnerability hypotheses in the context of neurodegenerative diseases such as Alzheimer's, Parkinson's, a n d ALS. It highlights the contributions of key researchers in the field, discusses the central role of proteins like tau, alpha-synuclein, and TDP-43, and examines the latest advancements in neuroimaging technologies. Our manuscript aligns with the aims and scope of Frontiers in Aging Neuroscience, as it offers a detailed analysis of two leading theories in neurodegeneration, a topic of immense importance in understanding aging-related cognitive decline. This submission contributes to the journal's mission of publishing cutting-edge research and disseminating knowledge on aging and neuroscience to a broad spectrum of readers, including researchers, clinicians, and the wider public. We believe that our manuscript will add significant value to your readership, especially with its focus on the latest research trends, protein-specific pathologies, and emerging imaging techniques in the study of neurodegenerative diseases.